Kajian Teologi Misi Terhadap Persembahan di Jemaat GMIM Alfa Omega Rinegetan Wilayah Tondano II - Mantiri, Syalomitha Fabiola; Sarimbangun, Ramli (Educatio Christi, 2021)
This thesis aims to conduct an in-depth study of Offerings in the Alfa Omega Rinegetan congregation in the perspective of Mission Theology. Offerings are a form of gratitude form believers and the offerings given by these believers are collected to sustain the work of church ministry which is part of the implementation of God’s Mission in this world. Making offerings, then, is one way as believers to assist in God’s missionary service through the church. However, the reality that occurs in the GMIM Alfa Omega Rinegetan congregation is that the lack of understanding and meaning of the congregation to give offering also affects the way they give. And in this study the author used qualitative research methods. The results of this study will explain the understanding of the congregation and the responsibility as believers in making offerings in order to help God’s mission work in this world through the church. The end of this paper is a conclusion that affirms the answer to the purpose of the study.